Strengthening the Character: Uphold Ethics in Indonesian Language Study Pass by Supplementary Books - Maryam, Siti (EDUCARE, 2012)
ABSTRACT: Nowadays, characters reinforcement matter has been taken into account for the sake of the nation. We can learn from other countries that succeed in managing education; so that the integration of character education in our country, Indonesia, must be conducted. For that objective, the writer assumes that supplementary books are facility usable for teacher of Indonesian language and literature subject to be exploited. Meanwhile, the effort of Indonesian language study teachers in strengthening student character and upholding ethics is one of effort in improving human resource quality. This effort is very essential, considering the quality of Indonesian citizen is still unsatisfying. Through speaking and writing skills, teacher can evaluate the use of language ethics among students, both directly and indirectly. This article aims to present a study of optimizing language learning to form studentsâ character and ethics. By combining creativity, character, and ethics to Indonesian language and literature learning, the writer optimizes also implicitly the role and function of Indonesian language and literature learning in accordance to its target, among others for character and students language ethics reinforcement. So, students as the next generation should be prepared to socialize and live properly. Therefore, Indonesian language and literature learning should optimize the studentsâ role through supplementary books.Â Â  KEY WORDS: Character education, teaching and learning process, supplementary books, Indonesian language, and students as the next generation.About the Author: Dr. Hj. Siti Maryam is a Senior Lecturer at the Department of Indonesian Language Education, Faculty of Education and Teacher Training UNSUR (University of Suryakancana) in Cianjur, West Java, Indonesia. She can be reached at: yams1964@yahoo.comHow to cite this article? Maryam, Siti. (2012). âStrengthening the Character: Uphold Ethics in Indonesian Language Study Pass by Supplementary Booksâ in EDUCARE: International Journal for Educational Studies, Vol.5(1) August, pp.39-50. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 18, 2012); Revised (July 20, 2012); and Published (August 17, 2012).